2022
DOI: 10.1155/2022/5689900
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Periodontal Endodontics Combined with Diode Laser (DL) Therapy on Severe Periodontitis

Abstract: Background. For a long time, the impact of severe periodontitis on the pulp has been the focus of periodontal clinical research. Whether the teeth with severe periodontitis should be treated with pulp has also become the focus of clinical research. Aims. To explore the effect of periodontal endodontic therapy combined with DL therapy on severe periodontitis. Materials and Methods. The clinical data of 100 patients with severe periodontitis from January 2020 to July 2022 were selected and included in the retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%